2005
DOI: 10.1021/es0489543
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Humic Substances by Environmental Scanning Electron Microscopy

Abstract: Environmental scanning electron microscopy (ESEM) is a new technique capable of imaging micron and submicron particles. Here, we have applied it to image and quantify natural aquatic organic matter (standard Suwannee River humic acid, SRHA). Uniquely, we have observed the humic aggregate structures as a function of humidity and pH. Large aggregates of tens of micrometers were observed as the dominant material under all conditions, although much smaller material was also observed. Fractal dimensions (D) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…However, care must be taken not to drastically change the nature of the samples. The present work showed no evidence that changes in the sample structure or aggregation had taken place, but Redwood et al 29 demonstrated that material such as humic substances, the major organic constituents of soils and aquatic environments, 36,37 tend to aggregate when subjected to dehydration. Fig.…”
contrasting
confidence: 62%
See 3 more Smart Citations
“…However, care must be taken not to drastically change the nature of the samples. The present work showed no evidence that changes in the sample structure or aggregation had taken place, but Redwood et al 29 demonstrated that material such as humic substances, the major organic constituents of soils and aquatic environments, 36,37 tend to aggregate when subjected to dehydration. Fig.…”
contrasting
confidence: 62%
“…Another study that quantified the structures of standard Suwannee River humic acids using fractal dimensions 29 also observed the formation of large crystals of NaCl during dehydration of their NaCl-based sample matrix in ESEM, although those appeared differently shaped than in this study.…”
mentioning
confidence: 45%
See 2 more Smart Citations
“…Moreover, the low-density particles in the fractions would have had a relatively large size distribution. Electron microscope imaging of colloidal fractions Both TEM and SEM have often been used to visualise the size and shape of aquatic colloids and other particles (Wilkinson et al 1999;Redwood et al 2005). Here, the purified nanocolloid fractions were analyzed by TEM to validate laser granulometry measurements and assess the capability of CFF to retain nanocolloidal particles.…”
Section: Cff Performancementioning
confidence: 99%